Risk of cardiovascular disease according to blood pressure categories in an argentinian cohort - Salazar, Martín R. (2016)
Background: Hypertension is a recognized strong risk factor for cardiovascular disease. However, no data was available in our country to quantify the relationship between blood pressure and cardiovascular event. Objective: to quantify the risk of cardiovascular events according to blood pressure categories. Methods: A prospective epidemiological study was conducted in 1526 inhabitants from Rauch City, (Buenos Aires, Argentina) between 1997 and 2012. Subjects were classified into one of these blood-pressure categories: 1-optimal, 2-normal, 3-high-normal, 4-grade 1 hypertension, 5-grade 2 hypertension and 6-grade 3 hypertension. The first CVD event, including unstable angina pectoris, fatal and non-fatal myocardial infarction, myocardial revascularization, and fatal or non-fatal stroke, was defined as the primary endpoint. Multivariable Cox proportional-hazards regression models were used to estimate the relative risk (HR) of CVD according to base-line blood-pressure categories. Results: In 2012, 1124 individuals (73.7% of the baseline sample), 719 women and 405 men (in 1997, aged 45±16 and 46±16 respectively) or their relatives in case of death, could be surveyed again in order to obtain information concerning incident CVD events. Cardiovascular event rates and HR values increased in a stepwise manner across the blood pressure categories (p for trend across categories <0.001 in both sex); however, in subjects aged ≥55 years a j-curve phenomenon was observed, showing the lowest incidence in the high-normal category. In all categories CVD events rates were higher for men. Conclusion: This study quantified relationships between BP and CVD starting from high-normal blood pressure in Argentina.